Maternal age and trajectories of cannabis use. (1st November 2015) - De Genna, Natacha M.; Cornelius, Marie D.; Goldschmidt, Lidush; Day, Nancy L.
Graphical abstract: Highlights: This is the first study of maternal cannabis use spanning 17 years. Growth mixture modeling revealed four distinct maternal cannabis user groups. Younger mothers were less likely to be in the non/unlikely to use group. Younger mothers were more likely to be in the late desistance or increasingly likely/chronic user groups. Depressive symptoms also predicted increasingly likely/chronic maternal cannabis use. Abstract: Background: Becoming a mother is a developmental transition that has been linked to desistance from substance use. However, timing of motherhood may be a key determinant of cannabis use in women, based on preliminary evidence from teenage mothers. The goal of this study was to identify trajectories of maternal cannabis use, and to determine if maternal age was associated with different trajectories of use. Methods: This prospective study examined 456 pregnant women recruited at a prenatal clinic, ranging in age from 13 to 42 years. The women were interviewed about their cannabis use 1 year prior to pregnancy and during each trimester of pregnancy, and at 6, 10, 14, and 16 years post-partum. Results: A growth mixture model of cannabis use reported at each time point clearly delineated four groups: non/unlikely to use, decreasing likelihood of use, late desistance, and increasing likelihood/chronic use (Lo–Mendell–Rubin adjusted LRT test statistic = 35.7, p  < .001). The youngest mothers were least likely to be in the "non/unlikely to use" group. Younger maternal age also differentiated between late desistance and increasing likelihood/chronic use, versus decreasing likelihood of use post-partum. Conclusions: This is the first study to demonstrate that younger mothers are more likely to use cannabis across 17 years, including later desistance post-partum and increasing/chronic use. Other substance use and chronic depressive symptoms were also associated with more frequent use. These findings have implications for both prevention and treatment of cannabis use in mothers.